Incidence and risk factors for iatrogenic distal tibia/fibula fracture during Ponseti technique of clubfoot treatment. Issue 6 (November 2019) - Ranjan, Rahul; Sud, Alok; Adhikary, Debashis; Sinha, Abhinav; Chand, Suresh
Abstract : The incidence and risk factors of distal tibia/fibula fracture, an uncommon complication during Ponseti manipulation, are unknown. We evaluated 222 virgin clubfeet of patients aged less than 3 years for fractures of distal tibia/fibula. Incidence rate was found to be 1.3% per year. Associated risk factors were identified as neglected, syndromic clubfeet, feet requiring greater than 10 casts, post-tenotomy dorsiflexion less than 10° and casting by physician with less than 3 years of casting experience, with odds ratios of 14, 28, 4.9, 3.7 and 3.4, respectively. Most of these fractures healed without consequences; however, it is still advisable not to forcefully dorsiflex while casting, which may result in the fracture of distal tibia/fibula.